Analyzing the Necessities for Blended Learning in Higher Education: A Pathway to Flexible Learning - Faznah, Faznah; Khaerudin, Khaerudin; Tarjiah, Indina Tarjiah (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
Rapidly developing educational technology innovations require educational institutions to provide innovation in creating effective and efficient learning in order to achieve optimal educational goals. Blended learning is an alternative for institutions that still implement conventional learning to integrate technology into learning and overcome the problem of learning duration so that students can learn actively and flexibly. This study aims to collect information about student needs in designing a flexible blended learning model to optimize learning in learning media courses. Needs analysis is used to explore information about gaps, student needs, and the readiness of lecturers and institutions in creating a blended learning model. This study uses an exploratory research type. The population in this study sample is all PAI students with a sample used 28 students who have taken learning media courses. Data collection techniques are carried out by observation, interviews, and questionnaires. The data obtained are analyzed by descriptive qualitatively. The results of the study indicate that students need a more active and flexible learning system, this shows that a flexible blended learning model is one solution to increase the effectiveness of the learning process. The reason is, that 21st-century learning supports the realization of smart education by utilizing technology, namely internet-based learning to prepare students as prospective teachers in creating learning media that synergizes with 21st-century learning.